Peran Penting Dan Implementasi Empat Pilar Negara Pancasila Dalam Pembangunan Indonesia - Wiryadi Wiryadi; Arkaan Fadhlurrahman; Muhammad Alif Atasyah; Muhammad Ardan Aldika (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
In people's lives as Indonesian citizens, there are 4 pillars of the Pancasila State which are very important in the ideology and development of the country, which consist of Pancasila as the state ideology, the 1945 Constitution, the Republic of Indonesia in the form of the Republic of Indonesia which has the sovereignty of the people, Bhinneka Tunggal Ika as the state motto. , and mutual cooperation as the spirit of cooperation in society, is a strong foundation for the development of the Indonesian nation. In the context of development, the 4 Pillars of the Pancasila State provide clear direction and guidance for the government and society to achieve sustainable and inclusive development goals. By strengthening the values of Pancasila, respecting diversity, and implementing mutual cooperation in various areas of development, Indonesia can achieve sustainable progress and realize prosperity for all its people. challenges and opportunities in implementing the 4 Pillars of the Pancasila State in the context of Indonesian development, as well as providing recommendations to increase the effectiveness of this implementation. By contributing to understanding the importance of the 4 Pillars of the Pancasila State in guiding Indonesia's development towards a better future.